Multidisciplinary Approach of a Rare Case of Placenta Increta with Multiple Comorbidities: A Case Report - Trocadero, Lucian; BREZEANU, Dragoș; Brezeanu, Ana-Maria; Tica, Vlad-Iustin (International Journal of Innovative Research in Medical Science, 2024)
Background: The medical condition known as placenta increta was first described in 1937. If a pregnant woman experiences this condition, a multidisciplinary team that includes an obstetrician, surgeon, urologist, and anesthesiologist must address the case. Case Report: A 32-year-old woman, who has had two prior pregnancies, sought medical attention at our emergency department during her 28th week of gestation. She reported experiencing abdominal pain over the past two days and reduced vaginal bleeding for 12 hours. The patient was admitted to the hospital with a provisional diagnosis of placenta accreta and underwent Magnetic Resonance Imaging and multiple multidisciplinary consultations due to her numerous comorbidities. Despite a planned elective cesarean delivery scheduled for 34 weeks of gestation, the patient underwent an emergent cesarean delivery at 33 weeks due to heavy vaginal bleeding. Following the delivery of the baby, a subtotal hysterectomy was conducted while the placenta was left on site. Although an effort was made to preserve both ovaries, the bilateral adnexectomy was performed due to intense adherent syndrome and significant bleeding from both ovaries. After being hospitalized for nine days, the patient was discharged and followed up at 40 days and six months after surgery. The infant was also discharged 40 days after birth. The histopathological appearance was consistent with a diagnosis of placental increta. Conclusions: This presentation outlines a unique case of placenta increta, characterized by central placenta previa and velamentous cord insertion, that was associated with multiple comorbidities. Despite these challenges, the mother and the child made a full recovery.